2021
DOI: 10.1021/acs.jctc.1c00915
|View full text |Cite
|
Sign up to set email alerts
|

Dipole Moment Calculations Using Multiconfiguration Pair-Density Functional Theory and Hybrid Multiconfiguration Pair-Density Functional Theory

Abstract: The dipole moment is the molecular property that most directly indicates molecular polarity. The accuracy of computed dipole moments depends strongly on the quality of the calculated electron density, and the breakdown of single-reference methods for strongly correlated systems can lead to poor predictions of the dipole moments in those cases. Here, we derive the analytical expression for obtaining the electric dipole moment by multiconfiguration pair density functional theory (MC-PDFT), and we assess the accu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 126 publications
0
9
0
Order By: Relevance
“…To evaluate MC-PDFT dipole moments, we performed analytic differentiation of the MC-PDFT energy using Lagrange's method of undetermined multipliers. 158 This approach shares the same set of Lagrange multipliers as discussed in the previous section. Since the HMC-PDFT energy is a linear combination of the CASSCF and MC-PDFT energies, the HMC-PDFT analytic dipole moment comes with no additional cost compared to MC-PDFT.…”
Section: Dipole Momentsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate MC-PDFT dipole moments, we performed analytic differentiation of the MC-PDFT energy using Lagrange's method of undetermined multipliers. 158 This approach shares the same set of Lagrange multipliers as discussed in the previous section. Since the HMC-PDFT energy is a linear combination of the CASSCF and MC-PDFT energies, the HMC-PDFT analytic dipole moment comes with no additional cost compared to MC-PDFT.…”
Section: Dipole Momentsmentioning
confidence: 99%
“…To assess the performance of MC-PDFT for predicting dipole moments, we first explored dipole moments of diatomic molecules as functions of geometry. 158 Using a CASSCF calculation with a full-valence active space for the first step, we compared MC-PDFT with the tPBE on-top functional and HMC-PDFT with the tPBE0 functional to MRCI with single and double excitations and a quadruples correction (MRCISD + Q). For HF, CO, and NO, we found that the MC-PDFT and HMC-PDFT dipole moments were much closer to MRCI + Q than to CASSCF.…”
Section: Dipole Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the on-top second-order reduced density matrix represents the probability that two opposite-spin electrons are found at point r and integrates to the total number of interacting pairs. Multiconfiguration Pair-Density Functional Theory (MC-PDFT [29][30][31][32]) can be thus viewed as a post-MCSCF method that evaluates the energy of any state with on-top pair-density function theory. Basically, for a MCSCF wavefunction, |Ψ MCSCF = ∑ µ C µ |Ψ µ , one can obtain the total electronic energy as:…”
Section: Theories Going Beyond (Td-)dftmentioning
confidence: 99%
“…One powerful multireference method is the multiconfiguration pair-density functional theory (MC-PDFT), an electronic structure theory that evaluates the electronic energy from the multiconfigurational wave function using the kinetic energy, density, on-top pair density, and an on-top density functional. Recently, we derived 13 the analytic dipole moment expression for CAS-PDFT, which is MC-PDFT based on a CASSCF reference state. However, that treatment did not yield transition dipole moments.…”
Section: Introductionmentioning
confidence: 99%